(untitled) (Modern education and development, 2025)
This article focuses on the phenomenon of lexical meaning as a core element of the semantics of a word. The aim is to examine its nature, its distinction from grammatical meaning, and the various forms in which it can manifest. Special attention is paid to the denotational and connotational aspects of lexical meaning, its role in communication, and its dependence on cultural and contextual factors. This analysis is relevant not only to linguists but also to anyone interested in semantics, translation, or language teaching.